The role of exosomes in the pathogenesis and management of diabetic kidney disease: a systematic review and meta-analysis - Zheng, Yan; Xu, Chu; Jin, Yan (Frontiers in Endocrinology, 2024)
Objective This systematic review and meta-analysis aimed to synthesize the role of exosomes in the pathogenesis and management of diabetic kidney disease. Methods PubMed, Embase, Cochrane Library, and Web of Science were searched for studies that compared the levels of exosomes between patients with diabetic kidney disease and controls published up to 27 November 2023. Methodological quality was assessed using the JBI Appraisal Checklist for Case–Control Studies. The methodology of the samples and the main results were summarized. A meta-analysis of the diagnostic performance of exosomes was performed using estimates of test sensitivity and specificity, and these values were summarized using summary receiver-operating characteristic curves. The results were reported following the PRISMA 2020 checklist. Results A total of 32 studies, including 1,119 patients with diabetic kidney disease and 1,328 controls, met the inclusion criteria. A total of 78 upregulated and 22 downregulated microRNAs, 2 upregulated and 4 downregulated mRNAs, 6 upregulated and 1 downregulated proteins, and 4 upregulated lipids were identified. The miR-126, miR-145, miR-150, miR-21, and WT1 mRNA dysregulation were consistently reported in at least two studies. The overall sensitivity and specificity of the exosomes in diabetic kidney disease diagnosis were 0.70 (95% CI: 0.59–0.80) and 0.79 (95% CI: 0.70–0.85), respectively. The summary receiver operating characteristic curve was plotted to assess diagnostic accuracy with the area under the curve (AUC) of 0.82 (95% CI: 0.78–0.85). Conclusion Exosomes have great potential to become effective diagnostic biomarkers for diabetic kidney disease. Panels of exosomes or the combination of exosomes with other clinical indicators seemed more accurate than single exosomes.